FINANCIAL SITUATION OF COOPERATIVE BANKS IN POLAND IN THE YEARS 2022-2023 – THREATS AND RECOMENDATIONS - Sławomir Juszczyk (Annals of the Polish Association of Agricultural and Agribusiness Economists)
The aim of the research was to recognize the financial situation of the cooperative banking sector in Poland in the years 2022-2023, identify threats and formulate recommendations for these banks for the near future. The research analysed, among others, aspects related to the financial liquidity of these banks, their capital adequacy and solvency. In the course of the research, it was established, among others, that cooperative banks in Poland improved their position on the banking market in 2023, achieving a significant increase in net profit and other measures of financial efficiency. The threat to the cooperative banking sector in Poland is that the internal factors related to more effective management in these banks are mostly exhausted and in the future the possibilities of further improvement of financial efficiency through resource optimization are not large, which may be a barrier especially in future crisis situations. Further improvement of financial efficiency can be seen in more effective credit risk management, reducing the share of impaired loans in the portfolio and reducing financial reserves. In 2023, it was beneficial for cooperative banks that the greatest dynamics in their credit portfolio was observed in relations to the agricultural sector, where the previously observed trend in the scope of granting loans was reserved. In addition, in the last quarter of 2023 there was an increase in receivables in relation to the self-government sector which is therefore a relatively safe area of activity for cooperative bank.